The Role of Visual Audio Media as an Educational Innovation to Improve Understanding in Filling the PKK Log Book in Kasiman Village: A Needs Analysis Study - Dini Dwi Fajar Wati; Tri Murwaningsih; Fatma Sukmawati (Universitas Sebelas Maret, 2023)
It is undeniable that audio-visual media has now become one of the choices of media for conveying information or subject matter. Its flexible character-istics make it one of the top choices for pack aging information. Therefore, this study aims to identify the needs of the Kasiman Village PKK team to create a media for conveying information so that they have an understanding of how to fill out the PKK aid book. This research is included in the type of descriptive quantitative research, with a total of 49 research subjects. The in-strument used was a questionnaire, and was analyzed with percentages and descriptions. The results of the research revealed that so far most of the resi- dents who are part of the Village PKK team do not have an understanding of how to fill out the aid book, and do not understand their duties and responsi-bilities as members of the PKK, besides that they also do not have the main reference as information which is then used as the basis carrying out activi-ties or others. Besides that, the results of the analysis of this questionnaire al-so stated that they wanted an innovation in an audio-visual media that they could study so they would know how to fill out the village PKK aid book. The importance of providing clear guidelines and main references as guide-lines in carrying out duties and responsibilities as members of the Village PKK team.